Quantitative easing with bite: A proposal for conditional overt monetary financing of public investment - Andrew Watt (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
To address the on-going crisis in the euro area it is proposed to introduce a scheme of conditional, overt monetary financing of public investment (COMFOPI). The inadequate response of monetary and fiscal policy is shown to explain the weak performance of the euro area compared with other advanced countries since the crisis. The measures currently on the table, including the Juncker Plan and quantitative easing QE, are unlikely to bring about the needed substantial improvement in economic growth, while putting growth on a sustainable footing. Advantages and dangers of monetary financing of fiscal policy are discussed in the light of the recent literature. COMFOPI is a form of QE in which bonds newly issued by the European Investment Bank are purchased, on secondary markets, by the ECB, and the financial resources are made available to national governments to finance investment projects. The scheme is explicitly time-limited by being made subject to a price-stability criterion ("conditional"). The provision of central bank money leads directly to higher spending in the economy ("overt"), unlike with QE which relies on indirect channels. A number of ways to operationalise the scheme are discussed. – – Als Antwort auf die fortwährende Krise des Euroraums wird hier ein Vorschlag für die monetäre Finanzierung von öffentlichen Investitionen vorgestellt. Die schwache Performanz des Euroraums seit der Krise verglichen mit anderen entwickelten Volkswirtschaften ist im Wesentlichen dem Fehlen eines adäquaten Zusammenspiels von Geld- und Fiskalpolitik verschuldet. Die zur Zeit am Anfang der Umsetzung befindlichen Maßnahmen, nicht zuletzt der Juncker Plan und das Program der quantitativen Lockerung (QE) durch die EZB, werden vermutlich nicht in der Lage sein, den notwendigen Wachstumsschub zu erbringen und vor allem das Wirtschaftswachstum auf ein stabiles Fundament zu stellen. Vorteile und Gefahren der monetären Staatsfinanzierung werden vor dem Hintergrund der wissenschaftlichen Literatur herausgearbeitet. Die hier vorgeschlagene COMFOPI (Conditional, Overt Monetary Financing Of Public Investment) ist eine Form der quantitativen Lockerung, bei der die Europäische Investitionsbank neue Anleihen emittiert, die dann von der Europäischen Zentralbank auf Sekundärmärkten aufgekauft werden. Die EIB stellt die Ressourcen den Mitgliedsstaaten für öffentliche Investitionen zur Verfügung. Das Programm ist explizit befristet, da es bedingt ist durch ein Preisstabilitätskriterium (daher "conditional"). Das Zentralbankgeld führt aber, im Gegensatz zur QE, die sich indirekter Kanäle bedient, direkt zu erhöhter wirtschaftlicher Aktivität (daher "overt"). Einige Optionen bei der Umsetzung des Vorschlags werden diskutiert.
urn:nbn:de:101:1-2015032510767
Keywords: 330; Euro area; monetary financing; quantitative easing; European Central Bank; European Investment Bank; public investment; sustainable growth